Farmers as Innovators in Building Indigenous Knowledge Systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Valuing the Involvement of Civil Society in Enhancing the S&T Dialogue